Mode‐Locking of All‐Fiber Lasers Operating at Both Anomalous and Normal Dispersion Regimes in the C‐ and L‐Bands Using Thin Film of 2D Perovskite Crystallites - Hong, Seongjin; Lédée, Ferdinand; Park, Jaedeok; Song, Sanggwon; Lee, Hyeonwoo; Lee, Yong Soo; Kim, Byungjoo; Yeom, Dong‐Il; Deleporte, Emmanuelle; Oh, Kyunghwan (Laser & photonics reviews, 2018)
Two‐dimensional hybrid organic–inorganic perovskites have recently attracted attention in various optoelectronic applications. A novel thin film of 2D perovskite (C6H5C2H4NH3)2PbI4 crystallites is synthesized and its nonlinear optical properties are experimentally investigated within the optical gain of an Erbium‐doped fiber. Utilizing its unique nonlinear optical response, efficient mode‐locking of an all‐fiber Erbium laser is demonstrated at the anomalous dispersion regime in both the C‐ and L‐bands stably generating femtosecond pulse trains, where the thin film of 2D perovskite crystallites function as an in‐line saturable absorber. At this anomalous dispersion regime, self‐started femtosecond pulses are generated whose center wavelength are tuned from 1565.9 nm in C‐band and 1604 nm in L‐band by adjusting the optical gain. Furthermore, by managing the chromatic dispersion of the total fiber laser cavity to reach the normal dispersion regime, a stable dissipative soliton is successfully generated in the C‐band with the spectral bandwidth of 15 nm and pulse duration of 3.2 ps. Detailed material properties of the thin film of 2D perovskite crystallites, their characterization, and fiber laser mode‐locking performance is reported. A two‐dimensional crystallites perovskite ((C6H5C2H4NH3)2PbI4) is combined with a fiber laser to confirm its nonlinear optic functionality by generating an ultrafast laser in both transform‐limited soliton and dissipative soliton formats in the entire C‐ and L‐bands. It shows the shortest pulse width, the highest repetition rate, the most stable pulse generation, and the highest slope efficiency compared with 3D perovskite‐based pulse lasers.